2022
DOI: 10.1039/d2fd90062a
|View full text |Cite
|
Sign up to set email alerts
|

Concluding remarks: Challenges and future developments in biological electron cryo-microscopy

Abstract: CryoEM has made amazing progress during the past 10 years and is in a process of rapid transformation. This year’s Faraday Discussions examined some of the remaining challenges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
0
0
Order By: Relevance
“…Cryo EM technology, as a powerful tool in biomedical research, has shown great potential in the field of protein and macromolecular complex structure analysis. However, in the pursuit of deeper understanding of biomolecules, Cryo EM still faces many challenges, especially in sample preparation, data collection and processing (Kühlbrandt, 2022). The difficulty of sample preparation, especially in rapidly freezing samples to preserve their structure close to the original ecology without forming ice crystals, and finding suitable preparation methods for proteins that are difficult to express or stable, is a major challenge.…”
Section: Challenges and Prospectsmentioning
confidence: 99%
“…Cryo EM technology, as a powerful tool in biomedical research, has shown great potential in the field of protein and macromolecular complex structure analysis. However, in the pursuit of deeper understanding of biomolecules, Cryo EM still faces many challenges, especially in sample preparation, data collection and processing (Kühlbrandt, 2022). The difficulty of sample preparation, especially in rapidly freezing samples to preserve their structure close to the original ecology without forming ice crystals, and finding suitable preparation methods for proteins that are difficult to express or stable, is a major challenge.…”
Section: Challenges and Prospectsmentioning
confidence: 99%